Restorative Cautioning, Theories of Reintegration, and the Influence of Japanese Notions of Shame - Goold, Benjamin J. (2003)
This article explains some of the central notions of restorative justice, drawing particular attention to the influence of Japanese notions of shame and community on cautioning practices in Britain and elsewhere